Evidence of apoptosis as an early event leading to cyclophosphamide-induced primordial follicle depletion in a prepubertal mouse model - Hao, Xia; Reyes Palomares, Arturo; Anastácio, Amandine; Liu, Kui; Rodriguez-Wallberg, Kenny A. (Frontiers in Endocrinology, 2024)
Introduction The mechanisms leading to ovarian primordial follicle depletion following gonadotoxic chemotherapy with cyclophosphamide and other cytotoxic drugs are currently understood through two main explanatory theories: apoptosis and over-activation. Discrepancies between the findings of different studies investigating these mechanisms do not allow to reach a firm conclusion. The heterogeneity of cell types in ovaries and their different degrees of sensitivity to damage, cell-cell interactions, periodical follicle profile differences, model age-dependent differences, and differences of exposure durations of tested drugs may partially explain the discrepancies among studies. Methods This study used intact prepubertal mice ovaries in culture as study model, in which most follicles are primordial follicles. Histological and transcriptional analyses of ovaries exposed to the active metabolite of cyclophosphamide 4-hydroperoxycyclophosphamide (4-HC) were carried out via a time-course experiment at 8, 24, 48, and 72 h. Results 4-HC treated ovaries showed a significant decrease in primordial follicle density at 24 h, along with active DNA damage (TUNEL) and overexpressed apoptosis signals (cleaved-poly ADP ribose polymerase in immunohistochemistry and western blotting). Meanwhile 4-HC treatment significantly up-regulated H2ax, Casp 6, Casp 8, Noxa, and Bax in ovaries, and up-regulated Puma in primordial follicles (FISH). Discussion Our results indicated that cyclophosphamide-induced acute ovarian primordial follicle depletion was mainly related to apoptotic pathways. No evidence of follicle activation was found, neither through changes in the expression of related genes to follicle activation nor in the density of growing follicles. Further validation at protein level in 4-HC-treated prepubertal mice ovaries at 24 h confirmed these observations.